(untitled) (Raparin Journal of Humanities (RJH), 2024)
Performed music is an important and unique part of the world’s music center and its different situations are analyzed through several scientific theories. The Kurdish Music Center has its own efforts in the field of composing and distributing music and can be classified into different categories and by resorting to these scientific principles can be treated scientifically. Since the beginning of its establishment, Sulaymaniyah has been a city full of artistic products and various innovations. Therefore, working on this entity is an important task of scientific research and excavating the history of this invention requires more scientific research, especially since the state of scientific research in the field of music and analysis of production situations is not at the necessary level. This research is an examination of the musical works that have been distributed in the city of Suleimani. It also classifies and distinguishes works in terms of stage and style. Along with these is the analysis of each of the songs sampled by the researcher in terms of form, harmony, distribution of words and use of musical instruments